Morphology of carbon dioxide-hydrogen-cyclopentane hydrates with or without sodium dodecyl sulfate - Lim, Yu-An; Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Crystal Growth & Design, 2013)
In this study, effects of cyclopentane (CP) and sodium dodecyl sulfate (SDS) on the hydrate formation morphology were investigated. A gas mixture of 40.0 mol % carbon dioxide and 60.0 mol % hydrogen was used in an unstirred system with subcooling as the driving force. Experimental pressure is at 6.0 MPa and experimental temperatures used are at 275.65 and 277.65 K (Delta T = 15.15 and 13.15 K). Formation of hydrates started at the cyclopentane-liquid water interface. Cloud-like, equiaxed skewed dendritic, equiaxed orthogonal dendritic, long dendritic, and cactus-like crystals could be observed for the experiments in the absence of surfactants. Rapid hydrate formation was observed for the experiments with 0.9 mL CP with or without the presence of surfactants compared to the experiments with 0.45 mL CP system at the same experimental conditions. The addition of SDS had led to a change in the hydrate crystal morphology, forming fiber-like crystals from the hydrate layer. Hydrates had also shown affinity to metal surfaces and tend to grow rapidly because of better heat transfer capacity. Gas uptake measurements were found to correlate well with the morphological observations. On the basis of the morphological observations, the mechanism of the CO2-H-2-CP system in an unstirred system is presented.